2015
DOI: 10.5489/cuaj.2303
|View full text |Cite
|
Sign up to set email alerts
|

The association between renal tumour scoring system components and complications of partial nephrectomy

Abstract: Introduction: We evaluate the associations between 3 renal tumour scoring systems and their components with perioperative complications of partial nephrectomy. Methods: A consecutive cohort of partial nephrectomy patients was analyzed. Patient characteristics were abstracted from medical records. PADUA scores (preoperative aspects and dimensions used for anatomic classification), RENAL (radius exophyic/endophytic nearness anterior/posterior location scoring) nephrometry scores, and Centrality index (C-index) w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
19
0
5

Year Published

2016
2016
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(24 citation statements)
references
References 27 publications
0
19
0
5
Order By: Relevance
“…7,4,21 However, Desantis et al suggested that some clinical tumor features included in the nephrometry scores, such as clinical diameter and endophytic growth pattern, seem more predictive of complications than others do. 22 In the present study, nephrometry scores were not reported as they had been introduced in literature after the generation of this prospective database (2008). Nevertheless, all nephrometry tumor features, such as clinical diameter, growth pattern, polar site, localization including hilar location and side, were descripted and none of these significantly predicts surgical complications.…”
Section: Discussionmentioning
confidence: 99%
“…7,4,21 However, Desantis et al suggested that some clinical tumor features included in the nephrometry scores, such as clinical diameter and endophytic growth pattern, seem more predictive of complications than others do. 22 In the present study, nephrometry scores were not reported as they had been introduced in literature after the generation of this prospective database (2008). Nevertheless, all nephrometry tumor features, such as clinical diameter, growth pattern, polar site, localization including hilar location and side, were descripted and none of these significantly predicts surgical complications.…”
Section: Discussionmentioning
confidence: 99%
“…Notably, the total PADUA score performed slightly better than the other systems for WIT and, unsurprisingly, correlated with the absolute change of eGFR after surgery. Desantis et al recently reported data of 118 patients diagnosed with clinically localised renal tumours in a single Canadian Institution. After adjusting for age and medical comorbidities, only the PADUA score was found to be significantly correlated with surgical (OR 1.31, P = 0.02) and overall (OR 1.12, P = 0.04) complications at ≤30 days of surgery.…”
Section: Discussionmentioning
confidence: 99%
“…Desantis et al . [ 25 ] reported PADUA score having significant correlation with surgical (OR 1.31, P = 0.02) and overall (OR 1.12, P = 0.04) complications at ≤30 days of surgery. This retrospective study included a cohort of 118 patients with clinically localized renal tumors and who underwent PN in a single institution.…”
Section: Discussionmentioning
confidence: 99%